LESBIAN, GAY, BISEXUAL, TRANSGENDER AGEING AND CARE: A LITERATURE STUDY - Henderson, Neil; Almack, Kathryn (Social Work/Maatskaplike Werk, 2016)
There is an increasing body of research on ageing and end-of-life care (EOLC) of lesbian, gay, bisexual and transgender (LGBT) older people in the UK, USA and Australia. In contrast, in South Africa, despite progressive legislation to protect LGBT rights, there has been minimal research in this area. This article reports on a critical review of literature on ageing of the LGBT community. Key themes identified include discrimination by health care workers and health risks for LGBT older people alongside the need for training of health professionals. The article concludes with consideration of the needs of LGBT persons in South Africa